Trajetória, dificuldades e permanência das mulheres no ensino superior - Baltieri, Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
It is common to read about the increase in the number of women entering higher education, but little is said about the dropout rate derived from the needs arising from the several journeys in their daily lives. It is necessary to understand what they actually go through and face, what mechanisms they use to reconcile their obligations, and how they fight to continue with their conquests. However, it is a fact that women have been conquering over time their place in universities and at work. Dealing with the problems that involve her in her triple journey as student, mother, housewife, and worker, a qualitative research will be carried out on the issue of these women's permanence inside the universities, in which situations they identify themselves, how the learning process occurs, which strategies they adopt to conciliate the triple journey, and what are the main difficulties they encounter, because it is analyzed that their mental health is affected by these several responsibilities that surround them. The study will show these journeys and their unfoldings based on research that points out these trajectories

É comum lermos sobre o aumento da entrada de mulheres no ensino superior, mas pouco se aborda sobre a desistência derivada das necessidades ocasionadas das diversas jornadas em sua vida diária. É preciso compreender o que elas de fato passam e enfrentam, quais mecanismos utilizam para conciliar suas obrigações, e como lutam para prosseguir com suas conquistas. Entretanto, é fato que a mulher vem conquistando com o passar do tempo seu lugar nas universidades e no trabalho. Tratando sobre a problemática que a envolve em sua tripla jornada de: estudante, mãe, dona de casa e trabalhadora, será realizada uma pesquisa qualitativa sobre a questão da permanência dessas mulheres dentro das universidades, em quais situações que elas se identificam, como se dá o processo de aprendizagem, quais estratégias adotadas para conciliar a tríplice jornada e quais são as principais dificuldades encontradas, pois analisa-se que sua saúde mental é afetada por essas diversas responsabilidades que as cercam. O estudo portanto, mostrará estes percursos e seus desdobramentos baseados em pesquisas que apontam estas trajetórias
Trajectories and permanence of women in higher education
Keywords: Woman; University; Difficulties; Triple journey; Permanence; Universidade; Dificuldades; Mulher; Tripla jornada; Permanência